2008
DOI: 10.1111/j.1461-9563.2008.00396.x
|View full text |Cite|
|
Sign up to set email alerts
|

Wheat stem sawfly‐infested plants benefit from parasitism of the herbivorous larvae

Abstract: 1 Parasitoids Bracon cephi (Gahan) and Bracon lissogaster Muesebeck and their herbivorous host the wheat stem sawfly Cephus cinctus Norton, a pest of wheat Triticum aestivum , were investigated for yield in T. aestivum grown in the field. 2 Wheat stem sawfly-infested stems had a higher yield potential than uninfested stems. However, final reproductive output was not significantly different between ears on infested stems that supported complete larval development compared with ears on uninfested stems. 3 Stems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…It emerged from a stub of red spring wheat that was cut by a C. cinctus larva. Therefore, we have confirmed that B. lissogaster is present in Canada and attacks C. cinctus as reported in the USA (Morrill et al 1998;Runyon, Hurley, Morrill, and Weaver 2001;Buteler, Weaver, and Miller 2008). The low numbers of B. lissogaster around the Lethbridge area likely represent a recent range expansion for this species.…”
Section: Please Scroll Down For Articlesupporting
confidence: 88%
“…It emerged from a stub of red spring wheat that was cut by a C. cinctus larva. Therefore, we have confirmed that B. lissogaster is present in Canada and attacks C. cinctus as reported in the USA (Morrill et al 1998;Runyon, Hurley, Morrill, and Weaver 2001;Buteler, Weaver, and Miller 2008). The low numbers of B. lissogaster around the Lethbridge area likely represent a recent range expansion for this species.…”
Section: Please Scroll Down For Articlesupporting
confidence: 88%
“…Also, in organic cropping systems, greater abundance and diversity of weeds can potentially provide more food and shelter for parasitoids of C. cinctus than fields conventionally managed where weeds are sprayed with herbicides. As a result of increased parasitoid pressure, C. cinctus survival and abundance can be reduced . While tillage kills C. cinctus larvae overwintering within wheat stems by burying the wheat stubble, it may also disproportionately kill parasitoids of C. cinctus if they overwinter belowground …”
Section: Introductionmentioning
confidence: 99%
“…Bracon cephi (Gahan) and Bracon lissogaster Muesebeck (Hymenoptera: Braconidae) are the only parasitoids that commonly attack C. cinctus in Triticum aestivum , reducing its survival and abundance . Both parasitoid species are specialists ( C. cinctus is the only host), idiobiont (prevent further development and kill the host), and ectoparasitoids (live externally on the host), with two generations per year .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wheat crops, these two species represent the only important insect natural enemies of C. cinctus, with B. cephi generally dominating (Runyon et al, 2002). These beneficial enemies can reach high densities and reduce economic damage by C. cinctus (Morrill et al, 1998;Buteler et al, 2008), but populations are highly variable across wheat fields and regions (Shanower and Waters, 2006) and causes of their population fluctuations are not well understood. The only documented host of the braconid parasitoids is C. cinctus, which is attacked during the larval stage regardless of whether host plants are crop or non-crop grasses.…”
Section: Introductionmentioning
confidence: 99%